2013
DOI: 10.1007/s00234-013-1202-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of brain proton MR spectroscopy and diffusion tensor imaging in newborns with hypoxic-ischemic encephalopathy treated by brain cooling

Abstract: Selective BC in HIE neonates does not affect the early and accurate prognostic value of ¹H-MRS and DTI, which outperform conventional MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 27 publications
1
41
1
Order By: Relevance
“…The predictive value of white matter integrity based on DTI for future outcome has been reported frequently in patient population such as preterm infants, stroke, TBI, and hypoxic-ischemic encephalopathy. 1,4,18,24 The findings in the current study add new value to the field demonstrating the predictive and prognostic value of DTI at a time shortly after surgical treatment (i.e. 3-month post-surgery) for outcomes measures assessed at a later time (12-month post-surgery).…”
Section: Discussionmentioning
confidence: 66%
“…The predictive value of white matter integrity based on DTI for future outcome has been reported frequently in patient population such as preterm infants, stroke, TBI, and hypoxic-ischemic encephalopathy. 1,4,18,24 The findings in the current study add new value to the field demonstrating the predictive and prognostic value of DTI at a time shortly after surgical treatment (i.e. 3-month post-surgery) for outcomes measures assessed at a later time (12-month post-surgery).…”
Section: Discussionmentioning
confidence: 66%
“…Advanced MRI methods such as DTI and MRS provide useful information about structural connectivity and altered brain chemistry, allowing improved detection of newborn brain injury over conventional MRI (3033). However, these strategies have limited ability to detect brain injury early enough whereupon it can guide clinical intervention within a therapeutic window (24, 25).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies [8,15] found that low ADC values in the corpus callosum were associated with an adverse outcome. These studies lacked other predefined study regions.…”
Section: Discussionmentioning
confidence: 99%